Inhaled Nitric Oxide Use in Pediatric Hypoxemic Respiratory Failure*. Issue 8 (August 2020) - Berger, John T.; Maddux, Aline B.; Reeder, Ron W.; Banks, Russell; Mourani, Peter M.; Berg, Robert A.; Carcillo, Joseph A.; Carpenter, Todd; Hall, Mark W.; Meert, Kathleen L.; McQuillen, Patrick S.; Pollack, Murray M.; et al.
Abstract : Objectives: To characterize contemporary use of inhaled nitric oxide in pediatric acute respiratory failure and to assess relationships between clinical variables and outcomes. We sought to study the relationship of inhaled nitric oxide response to patient characteristics including right ventricular dysfunction and clinician responsiveness to improved oxygenation. We hypothesize that prompt clinician responsiveness to minimize hyperoxia would be associated with improved outcomes. Design: An observational cohort study. Setting: Eight sites of the Collaborative Pediatric Critical Care Research Network. Patients: One hundred fifty-one patients who received inhaled nitric oxide for a primary respiratory indication. Measurements and Main Results: Clinical data were abstracted from the medical record beginning at inhaled nitric oxide initiation and continuing until the earliest of 28 days, ICU discharge, or death. Ventilator-free days, oxygenation index, and Functional Status Scale were calculated. Echocardiographic reports were abstracted assessing for pulmonary hypertension, right ventricular dysfunction, and other cardiovascular parameters. Clinician responsiveness to improved oxygenation was determined. One hundred thirty patients (86%) who received inhaled nitric oxide had improved oxygenation by 24 hours. PICU mortality was 29.8%, while a new morbidity was identified in 19.8% of survivors. Among patients who had echocardiograms, 27.9% had evidence of pulmonary hypertension, 23.1% had right ventricular systolic dysfunction, and 22.1% had an atrial communication. Moderate or severe right ventricular dysfunction was associated with higher mortality. Clinicians responded to an improvement in oxygenation by decreasing FIO2 to less than 0.6 within 24 hours in 71% of patients. Timely clinician responsiveness to improved oxygenation with inhaled nitric oxide was associated with more ventilator-free days but not less cardiac arrests, mortality, or additional morbidity. Conclusions: Clinician responsiveness to improved oxygenation was associated with less ventilator days. Algorithms to standardize ventilator management may improve signal to noise ratios in future trials enabling better assessment of the effect of inhaled nitric oxide on patient outcomes. Additionally, confining studies to more selective patient populations such as those with right ventricular dysfunction may be required. Abstract : Supplemental Digital Content is available in the text.